Funkcjonowanie audytu wewnętrznego po przystąpieniu Polski do UE - Antoniszyn, Emil (The Functioning of Internal Audit After Poland's Accession to the EU, 2008)
The preparation and afterwards the implementation of the projects from the EU structural funds require the fulfillment of definite conditions according the requirements of EU the legislation as well as of the suitable regulations of legal acts of the member country. This results, among other things, from fact that the financial funds given in the frames of structural funds are the public funds coming from the European Union budget, which consists of payments of every of the member states. According to this, the process of winning and utilization of these funds is covered by strict supervision, and the support can get only such projects, which fulfill definite conditions. In the documents of the European Committee the notion of audit is used often interchangeably with the notion of financial control. Under the notion of financial control would be understood: • abidance assurance of control procedures as well as execution of an preliminary opinion of advisability by financial obligations contraction and expenses making, investigation and comparison of actual state with the required state, taking and accumulating the public funds, contraction of the financial obligations and making public funds expenses, giving the public orders as well as the return of public funds, leading of financial economy as well as applying of the control procedures. On the basis of the European Committee decision, the organization SIGMA in the study Basis of the Financial Control proposed four criterions of financial control for new EU member countries, among them for Poland. SIGMA's Support for Improvement the in Governance and Management (Polish - Wsparcie uprawnień w rządzeniu i zarządzaniu) is the common initiative of OECD and the EU undertaken in 1992 for the support of reforms in public administration in the countries of Centraland Eastern Europe being the candidate to the EU. (Thorough theoretical bases were worked out in an interesting way in the area of audit by the authors: Alvin A. Arens and James K. Loebbecke in the book "Auditing an Integrated Approach" (Fifth Edition) Prentice Hall Englewood Cliffs, New Jersey 07632, /99/ by Prentice - Hall, Inc.). More important is the phase of audit realization, during which the sample of total undertaken expenses should be verified, permitting to give the auditor an binding opinion and to prepare a report in this area. The opinion or report should show the threshold of the significance and the level of trust according to the international standards. Therefore the audit should be conducted according to the international audit standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 13-27